Analisis Strategi Pemasaran dalam Meningkatkan Minat Beli Konsumen di PT Indomaret Pattimura Kota Gunungsitoli - Preti Insafkah Telaumbanua; Nov Elhan Gea; Yupiter Mendrofa; Maria Magdalena Bate'e (Jurnal Publikasi Manajemen Informatika, 2024)
Consumer behavior has seeped into the habits of all levels of society, regardless of their social class. Current developments have also triggered increasingly fierce competition in the retail sector, which requires business actors to optimize all their abilities and strategies in order to survive in increasingly fierce competition. This research method is a qualitative approach, researchers use data collection techniques by observation, interviews and documentation. The lack of marketing strategy at PT. Indomaret Pattimura, Gunungsitoli City causes an obstacle in attracting consumer buying interest. This research aims to find out how the marketing strategy is carried out by PT. Indomaret Pattimura, Gunungsitoli City. Based on the research results, it was concluded that PT. Indomaret Pattimura Kota Gunungsitoli has significantly utilized digital technology and promotional strategies to maintain and attract consumer buying interest. However, there is a need to improve the evaluation and effectiveness of technology training, as well as diversify promotional strategies to make them more attractive to various consumers. Attractive packaging, discounts, and friends' recommendations also play an important role in consumer shopping decisions. Even though the existing marketing strategy is quite effective, PT. Indomaret Pattimura Kota Gunungsitoli must continue to pay attention to product quality and diversity of offers to increase overall customer satisfaction. The application of technology in operations, use of social media, and massive promotions show the company's proactive efforts in facing competition.